Increased Force Required With Proposed Standardized Enteral Feed Connector in Blenderized Tube Feeding. (December 2016) - Mundi, Manpreet S.; Epp, Lisa; Hurt, Ryan T.
Background: Enteral tube misconnections resulting in enteral nutrition being provided into the wrong port or tube has been increasingly reported, prompting the development of new international design standards for medical device tubing connectors. Methods: Four sample enteral feeds with varying viscosity were placed into a syringe with either the current feeding connector or a prototype ENFit connector. The force (N) required to compress the syringe was gathered through a dynamic mechanical analyzer (RSA G2 Solids Analyzer; TA Instruments). Results: The force needed to compress the syringe was lowest with a fiber-containing formula (Jevity 1 Cal, Abbott Nutrition, Columbus, OH), and a decline in force was detected with the ENFit compared with the current connector (8.61 ± 0.27 N vs 9.62 ± 0.23 N, P < .001). A commercial blenderized formula (Liquid Hope, Functional Formularies, Centerville, OH) required slightly higher force with the ENFit than the current connector (16.82 ± 1.23 N vs 14.5 ± 0.03 N, P < .001). Another commercial blenderized formula (Salmon, Oats, & Squash, Real Food Blends, Chesterton, IN) and a homemade blenderized recipe required significantly more force with the ENFit than the current tube (34.12 ± 0.95 N vs 22.91 ± 0.06 N, P < .001; 34.95 ± 0.06 N vs 27.72 ± 0.07 N, P < .001, respectively). Conclusion: ENFit adapter implementation is the largest change to home enteral nutrition in more than a decade. Additional rigorous testing is required to ensure that the needs of all patients receiving home enteral nutrition are met prior to widespread adoption.